GRAPHIC INTENTIONS OF COLOR BLENDING IN INDIAN COMICS: भारतीय चित्रकथाओं (काॅमिक्स) में रंग सयोजन के ग्राफिक अभिप्राय - Kumar, Brijesh (International Journal of Research -GRANTHAALAYAH, 2014)
Graphic intent based on color combination is a systematic and managerial thought stream called combination in the language of art. Which is related to the different problem intervals and dividing into regions and arranging the selection of lines, shapes, colors (colors), tano and veins, etc. The history of the combination of colors in the story (comics) has been very old. When man first opened his eyes, he hunted in the middle of the natural environment and started filling his stomach. As a result, looking at its natural environment, it made the medium to convey its message on the walls of stones, rocks, caves, etc., coal, stones and nature colors. Knowledge of its size and medium is an important fact when drawing all the colors used in a painting. The use of veins in paintings produces a combination with the idea of ​​cool light or heat and coldness. Which makes an important contribution in attracting any person. It is well known to like the combination of colors in illustration. In which, if we use a mixture of white, blue, brown or yellow colors in a scene depicting a peaceful gathering or a scene of peace, a beautiful combination will create a cool environment. While the combination of special exotic and warm environment by colors like red, orange, yellow, purple etc. will produce effects, it is more beneficial to use colors in pictures according to their cultural identity and situation. Which makes the importance of any scene more and more attractive. रंग संयोजन के आधार पर ग्राफिक अभिप्राय एक व्यवस्थित और प्रबन्धात्मक विचार धारा को कला की भाषा में संयोजन कहते है। जिसका विभिन्न समस्या अन्तराल और क्षेत्रों में विभाजित करने एंव रेखाओं, आकृतियों, वर्णो (रंगों), तानो तथा वयन आदि के चयन को व्यवस्थित करने से सम्बधित है।चित्रकथा (काॅमिक्स) में रंगों का सयोजन का इतिहास काफी पुराना रहा है। मानव ने जब सर्वप्रथम आँखे खोली तो वह प्राकृतिक वातावरण के बीच रहते हुए शिकार करके अपना पेट भरने लगा। परिणाम स्वरूप अपने प्राकृतिक वातावरण को देखकर उसने पत्थरों, चट्टानों, गुफाओं आदि की दीवारांे पर कोयले, पत्थर तथा प्रकृति प्रद्दत रंगों को अपने संदेश सम्प्रेषित करने का माध्यम बनाया। चित्रकथा मंे प्रयुक्त सभी रंगों को चित्र बनाते समय उसके आकार और माध्यम का ज्ञान महत्वपूर्ण तथ्य है। समान प्रकाश छाया अथवा उष्णता कर शीतलता आदि के विचार से चित्रों में रगों का प्रयोग संयोजन उत्पन्न करता है। जो किसी भी व्यक्ति को आकर्षित करने में एक महत्वपूर्ण योगदान रखते है। इलैस्ट्रेशन में रंगों के सयोजन को पसन्द करना सर्वविदित है। जिसमें यदि हम किसी शान्त सभा या शान्त रस प्रदर्शित दृश्य को चित्रण में श्वेत, नीले, भूरे अथवा पीले रंगेां के विभिन्न मिश्रिणों का प्रयोग सुन्दर संयोजन शीतल वातावरण की सृष्टि करेगा। जबकि लाल नारंगी, पीले, बैगनी आदि रंगों द्वारा विशेष आलोकिक एंव उष्ण वातावरण का संयोजन प्रभाव उत्पन्न करेगा चित्रों में रंगो का प्रयोग उसकी सास्कृतिक पहचान उसकी स्थिति और प्रांसागिकता के अनुसार करना ज्यादा लाभदायक रहता है। जो किसी भी दृश्य के महत्व को ज्यादा और ज्यादा आकर्षक बनाता है।